Educational problems facing the teachers of remote villages schools in Tabuk region - Alblwi, Sarah Mohamad Mahdi (Journal of Educational and Psychological Sciences, 2022)
The study aims at identifying the problems facing teachers in remote village schools in Tabuk region. These problems were divided into four sectors: (Personal problems related to the teacher, problems related to the surrounding environment of the school, problems related to the environment within the school, and problems related to school administration). The study also reveals significant statistical differences in the means of responses of the teachers attributed to certain variables (years of experience, residence location, age and social status). In order to achieve the objectives of the study, the descriptive approach was used and the questionnaire was adopted as the survey tool. The study population consisted of school teachers at remote villages in Tabuk region, and the sample of the study was chosen randomly to be (300) teachers out of (454) teachers. The study concluded the following: The educational problems facing teachers at remote village schools in Tabuk region which are related to the surrounding environment of school came in the first place with a very high level and average of (4.49); the personal problems came in the second place with a very high level and average of (4.34); the problems related to environment within the school came in the third place with a high level and average of (4.12); and finally, the problems related to school administration came in the fourth place with a high level and arithmetic mean of (3.85). The study also shows that there are statistically significant differences attributed to the variable of residence (migrants, non-migrants) for all axes of the study. The study also indicates the absence of statistically significant differences attributed to the variables (years of experience, age, and marital status) for all axes of the study. The study recommends that the Ministry of Education take actions towards providing adequate housings for teachers willing to relocate to remote villages and issue circulars specifically for schools there, taking into account the conditions of these schools and the problems they suffer from.